Água: direito fundamental - AMIN, Aleph Hassan Costa (Universidade Federal do Pará, 2015)
Pollution and disordered use of water resources, gradually, are making water improper for human consumption. Moreover, both population and economic growth multiply the uses of water and make its demand to grow before an inelastic supply. The combination of these factors leads to infer that this resource can not be understood as an infinite good, since the confrontation of their availability with their demands tends to cause a shortage. In this context, it is clear that water, as a natural resource, is necessary for social development, andfor the economy too. For this reason, this study seeks to discuss the social and economic value of water, demonstrating how these values manifest themselves in a scenario of scarcity. Theapproach is made based on the fundamental rights, equating the access to water the list of rights.